de Amro Bank collectie : een keuze. - Beeren, W.A.L.; Meys, Th. A.J.; Rothuizen, William (Amsterdam : Stedelijk Museum Amsterdam, 1989)
Akkerman, Ben ; Andriesse, Erik ; Armando ; van den Ban, Hans ; Berkulin, Arie ; Blom, Ansuya ; Breedveld, Marian ; de Bueger, Chris ; Cardena, Michel ; Claassen, Johan ; Constant ; Content, Eli ; Couzijn, Wessel ; Daniels, René ; Dibbets, Jan ; Diederen, Jef ; Dieleman, Piet ; van den Dobbelsteen, Jan ; Dumas, Marlene ; Egberts, Otto ; van Elk, Ger ; Freijmuth, Alphons ; Haagmans, Fons ; van Haaster, Bettie ; van Hoek, Hans ; Kuijpers, Theo ; Lataster, Ger ; Leutscher, Hans ; Loerakker, Bert ; Lucassen ; Lucebert ; Luik, Hieke ; Makkink, Herman ; van Munster, Jan ; van Oord, Johan ; Oudshoorn, Reinoud ; Ploeg, Maarten ; Pol, Jan Van der ; Postma, Hannes ; van der Putten, Hendri ; Roeland, Jan ; Ruijgrok, Marc ; Sanders, Willem ; Schierbeek, Michiel ; Schoonhoven, Jan ; Struycken, Peter ; Teeken, Toon ; de Vaal, Elizabeth ; Veneman, Peer ; Verhoef, Toon ; Verkerk, Emo ; Verwiel, Jos ; Visch, Henk ; Visser, Carel ; Volten, André ; Vonck, Irene ; Vroegindeweij, Leo ; de Vroom, Henk ; Ysbrant
de Amro Bank collectie : een keuze, Stedelijk Museum Amsterdam, 9 december 1989 - 21 januari 1990
Nederlands
boek